(untitled) (CAHIERS MAGELLANES-NS, 2024)
Education has played a vital role in bringing desired changes in the society of Darjeeling hills. The main purpose of the study is why the Christian missionaries during the mid-19th century spread western education and how it brought a change in the society. When the missionaries came to Darjeeling how was the reaction of the people and their approach towards the western education. When the British took over Darjeeling Hills popular education was practically unknown .It was the missionaries who took the initiative of opening schools in different parts of Darjeeling district. Education which plays a very important role in moulding the character of an individual and a source from which one get information and knowledge has brought a tremendous change in the society of Darjeeling during the colonial period